2009
DOI: 10.1002/hipo.20644
|View full text |Cite
|
Sign up to set email alerts
|

IP3 mobilization and diffusion determine the timing window of Ca2+ release by synaptic stimulation and a spike in rat CA1 pyramidal cells

Abstract: Synaptically activated calcium release from internal stores in CA1 pyramidal neurons is generated via metabotropic glutamate receptors by mobilizing IP3. Ca2+ release spreads as a large amplitude wave in a restricted region of the apical dendrites of these cells. These Ca2+ waves have been shown to induce certain forms of synaptic potentiation and have been hypothesized to affect other forms of plasticity. Pairing a single backpropagating action potential (bAP) with repetitive synaptic stimulation evokes Ca2+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Once CICR is initiated, regenerative propagation will continue provided that IP 3 is available; the level of IP 3 at rest is not sufficient. The requirement for co-activation by IP 3 and Ca 2+ makes regenerative Ca 2+ release a coincidence detector for metabotropic glutamate receptor (mGluR) or muscarinic acetylcho-line receptor (mAChR) activation (which mobilizes IP 3 ) and postsynaptic Ca 2+ signalling (from bAPs or dendritic Ca 2+ spikes) in pyramidal neurons 17,22,38 and Purkinje neurons 39 . The timing window for this synergistic response varies from 100 to 500 ms 17,38,39 .…”
Section: Ca2+ Wavesmentioning
confidence: 99%
See 2 more Smart Citations
“…Once CICR is initiated, regenerative propagation will continue provided that IP 3 is available; the level of IP 3 at rest is not sufficient. The requirement for co-activation by IP 3 and Ca 2+ makes regenerative Ca 2+ release a coincidence detector for metabotropic glutamate receptor (mGluR) or muscarinic acetylcho-line receptor (mAChR) activation (which mobilizes IP 3 ) and postsynaptic Ca 2+ signalling (from bAPs or dendritic Ca 2+ spikes) in pyramidal neurons 17,22,38 and Purkinje neurons 39 . The timing window for this synergistic response varies from 100 to 500 ms 17,38,39 .…”
Section: Ca2+ Wavesmentioning
confidence: 99%
“…The requirement for co-activation by IP 3 and Ca 2+ makes regenerative Ca 2+ release a coincidence detector for metabotropic glutamate receptor (mGluR) or muscarinic acetylcho-line receptor (mAChR) activation (which mobilizes IP 3 ) and postsynaptic Ca 2+ signalling (from bAPs or dendritic Ca 2+ spikes) in pyramidal neurons 17,22,38 and Purkinje neurons 39 . The timing window for this synergistic response varies from 100 to 500 ms 17,38,39 . The duration of the window is closely related to the lifetime of IP 3 in the dendritic region where the wave is generated, which is determined by a combination of IP 3 degradation, IP 3 diffusion and IP 3 unbinding from the receptor 38,40 .…”
Section: Ca2+ Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifetime of an Ins(1,4,5)P 3 molecule is determined chiefly by its rate of metabolism, and possibly by the presence of Ins(1,4,5)P 3 buffering proteins. The functional lifetime of an Ins(1,4,5)P 3 molecule is also subject to passive diffusion [87]. As locally generated Ins(1,4,5)P 3 equilibrates in a cell, its concentration may fall below its affinity for binding ITPR, silencing the signal.…”
Section: Itpks Regulate Ins(145)p 3 Lifetimementioning
confidence: 99%
“…One recent study examined Ins(1,4,5)P 3 lifetime in CA1 pyramidal neurons using hippocampal slices and Ins(1,4,5)P 3 released by photolysis [87]. They concluded that the major determinant of the timing window for Ins(1,4,5)P 3 -regulated coincidence detection with action potentials was simply Ins(1,4,5)P 3 diffusion, rather than metabolism.…”
Section: Regulation Of F-actin By Itpka In Dendritic Spinesmentioning
confidence: 99%